2015
DOI: 10.1183/16000617.00000815
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary endarterectomy: the potentially curative treatment for patients with chronic thromboembolic pulmonary hypertension

Abstract: Pulmonary endarterectomy (PEA) is the treatment of choice to relieve pulmonary artery obstruction in patients with chronic thromboembolic pulmonary hypertension (CTEPH). It is a complex surgical procedure with a simple principle: removal of obstructive thromboembolic material from the pulmonary arteries in order to reduce pulmonary vascular resistance, relieve pulmonary hypertension (PH) and alleviate right ventricular dysfunction. In the majority of patients there is symptomatic and prognostic benefit. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
133
0
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 44 publications
3
133
0
14
Order By: Relevance
“…It is a surgically demanding technique and requires experience for the assessment of operability as well as technical skills for its performance. There are only a few centres worldwide with a case load > 1000 interventions and its delicate postoperative surveillance necessary to obtain a perioperative mortality < 5 % [15]. An expert centre is by defi nition one that performs at least 20 PEA operations per year with a mortality rate of < 10 %.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…It is a surgically demanding technique and requires experience for the assessment of operability as well as technical skills for its performance. There are only a few centres worldwide with a case load > 1000 interventions and its delicate postoperative surveillance necessary to obtain a perioperative mortality < 5 % [15]. An expert centre is by defi nition one that performs at least 20 PEA operations per year with a mortality rate of < 10 %.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Most patients will have haemodynamic abnormalities at rest, but in selected cases, patients with markedly increased pulmonary vascular resistance upon exercise have shown to benefi t from surgical intervention [15]. It must be underscored that patients should be evaluated only by an expert team in PEA before operations may be withheld.…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Vascular injury, including vascular endothelial injury, smooth muscle cell proliferation and vascular remodeling, is the basic pathological change of hypertension diseases (6)(7)(8). A previous study demonstrated that vascular endothelial injury is important in the development of hypertension (9).…”
Section: Introductionmentioning
confidence: 99%